2009
DOI: 10.1111/j.1365-2427.2007.01878.x
|View full text |Cite
|
Sign up to set email alerts
|

Sampling groundwater fauna: efficiency of rapid assessment methods tested in bores in eastern Australia

Abstract: Summary 1. Growing recognition of the ecological significance and biodiversity of groundwater fauna in Australia has led to statutory requirements for monitoring these communities prior to resource development. However, the efficiency of methods for assessing community composition and taxa richness remains untested, hampering the collection of reliable data for compliance. 2. We assessed the efficiency of two commonly‐used methods to sample groundwater fauna (net hauls and pumping) in bores in two contrasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 27 publications
1
58
0
Order By: Relevance
“…Sampling effort and sampling methodology can produce different species richness estimations (Hancock and Boulton, 2009). The latter authors demonstrated that a single sampling collected 30-87 % of the total species.…”
Section: Microcrustaceans In the Alpine Karstic Aquifermentioning
confidence: 99%
“…Sampling effort and sampling methodology can produce different species richness estimations (Hancock and Boulton, 2009). The latter authors demonstrated that a single sampling collected 30-87 % of the total species.…”
Section: Microcrustaceans In the Alpine Karstic Aquifermentioning
confidence: 99%
“…Groundwater (300 L) was pumped and passed through a 63-mm mesh sieve to collect stygofauna following Hancock and Boulton (2009). The sieve contents were preserved in 100% ethanol, stained with Rose Bengal, and later sorted under a microscope (Â60 magnification).…”
Section: Stygofauna Sampling and Analysismentioning
confidence: 99%
“…Geological history is thought to have a major influence on stygofauna composition, due to its role in supporting evolutionary divergence of species through isolation (Boulton et al 2003;Humphreys 2008;Griebler and Lueders 2009). Geology and water quality influence biotic distribution as they determine water flow, energy exchange, and habitat structure Hahn 2006;Hancock and Boulton 2009;Griebler and Lueders 2009). Other influences on the distribution of groundwater biota include climate, vegetation, water quality, links with the hyporheic zone, and human activities (Galassi et al 1999a(Galassi et al , 1999bCho and Kim 2000;Jasinska and Knott 2000;Schmidt et al 2007;Tomlinson 2008;Griebler and Lueders 2009;Hahn and Fuchs 2009;Stein et al 2010; Korbel et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…More sophisticated methods are urgently needed (Gutjahr et al, 2013;Hancock and Boulton, 2009). Until it is possible to sample at the relevant scales, most theoretical understanding will have to come from modelling (section 4.3).…”
Section: Sampling Micro Scale Variabilitymentioning
confidence: 99%